Acanthosis nigricans as a clinical marker of insulin resistance among overweight adolescents - Videira-Silva, Antonio (2019)
© 2019 Annals of Pediatric Endocrinology & Metabolism. This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.